Uso de modelos aditivos para evaluar la variabilidad espacial y temporal en datos 3D (2010)
This paper is aiming to identify the presence of variability over time and space for water temperature in Santa Marta, Colombia. The modeling process consider an approach through linear models, the use of additive models as an alternative to capture nonlinear patterns, evaluation of the need for a non parametric eﬀect for each of the covariates and ﬁnally, a diagnostic test for the residuals to assess the need to include a covariance structure over time and/or space.